Reproductive biology of the invasive exotic shrub, Rhododendron ponticum L. (Ericaceae) - STOUT, JANE CATHERINE (Blackwell, 2007)
The reproductive biology of an exotic species will affect its ability to become naturalized and invasive in non-native habitats. Rhododendron ponticum is an ecologically damaging exotic weed in the British Isles, which spreads predominantly by seed. I investigated how inbreeding and outcrossing affect seed production and germination in a wild population of this species in Ireland. Experimental manipulations revealed low fruit and seed set when insects were excluded from flowers, suggesting that this species has limited capability for spontaneous autogamy. Hand-pollination treatments showed that, although flowers are self-compatible (with self and same plant pollen), higher levels of seed set occur following outcrossing (xenogamy). There was no significant difference in rate of germination of seeds from inbred or outcrossed treatments. The addition of xenogamous pollen to open flowers did not increase fruit or seed set, suggesting that flowers in this population are not pollen limited: native generalist pollinators, mainly bumblebees (Bombus spp.), are providing an adequate pollinator service. This work demonstrates that outcrossing increases seed set and pollinators are required to facilitate this. Hence, generalist native pollinators can promote invasion by exotic plants. Native pollinators can clearly play an important part in alien species invasion.
PUBLISHED
Keywords: fruit set; hand pollination; inbreeding; invasion; outcrossing; pollination; seed production